2019
DOI: 10.1080/16549716.2019.1685809
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and predictors of normal-weight central obesity– the AWI-Gen study findings

Abstract: Background: Normal-weight central obesity is associated with higher mortality than general obesity as defined by body mass index, particularly in the absence of central fat distribution. Objective: The aim of this study was to examine the magnitude and predictors of normalweight central obesity in an urban informal settlement setting in Kenya. Methods: We used data from the AWI-Gen study, a cross-sectional survey targeting randomly selected consenting adults between the ages of 40-60 in two urban informal sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
3
19
1
Order By: Relevance
“…Similarly, women had higher measures of abdominal obesity compared to men. Our findings confirm what has been reported in other studies [ 17 , 19 – 21 ]. Likely reasons for this observation include that women are physiologically more predisposed to overweight and obesity due to the changes occurring during the reproductive years, and women have been reported to engage in less physically strenuous/demanding activities in the moderate to vigorous range compared to men in the same setting [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, women had higher measures of abdominal obesity compared to men. Our findings confirm what has been reported in other studies [ 17 , 19 – 21 ]. Likely reasons for this observation include that women are physiologically more predisposed to overweight and obesity due to the changes occurring during the reproductive years, and women have been reported to engage in less physically strenuous/demanding activities in the moderate to vigorous range compared to men in the same setting [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…Likely reasons for this observation maybe due to women’s physiologic makeup and the changes that occur during women’s reproductive years that may predispose them more to some of the conditions reported in this study such as overweight and obesity [ 28 ]. A study in the same setting also reported that women engaged more in sedentary activities and had higher levels of general obesity and normal-weight central obesity compared to men, which may predispose them to other chronic conditions [ 29 30 ]. Other reasons include women’s greater use of health facilities thus providing an opportunity for an increased chance for diagnosis of illness [ 31 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found that 19% of the patients with a normal BMI was in fact VO. In literature it is known that 18-34% of patients with a normal BMI has to much visceral fat [22]. In our previously study in colorectal patients 44% of patients with a normal BMI was visceral obese.…”
Section: Discussionmentioning
confidence: 68%